P458 Effectiveness of biological therapy for pouchitis and other inflammatory complications ot the pouch. And the question of a second Anti-TNF after failure? Results from the RESERVO Study of GETECCU. (27th May 2021) - Mesonero Gismero, F; Zabana, Y; Fernández-Clotet, A; Núñez, A; Caballol, B; Sola, A; García, M J; Bertoletti, F; Mínguez, A; Suris, G; Casis, B; Ferreiro-Iglesias, R; et al.
Abstract: Background: Pouchitis and Crohn′s-like disease of the pouch (CDP) can be refractory to conventional therapy. Evidence of biological therapy has been rarely reported in large patient cohorts. We explored the use and effectiveness of these therapies and compared the success of a second biologic after antiTNF failure. Methods: This is a retrospective RESERVO study of the Spanish cohort of GETECCU, that included patients operated for ulcerative colitis, with pouch construction, and subsequent diagnosis of pouchitis, CDP or cuffitis second ECCO diagnostic criteria 1 . Patients treated with antiTNF, Vedolizumab and/or Ustekinumab were selected. Clinical effectiveness was evaluated at long-term. We defined clinical remission as returning to the previous stool frequency, no pain or defecatory urgency, clinical response as the improvement in these parameters without the achievement of remission and non-response as no change or worsening of these symptoms. We also compared the effectiveness of second biologic (antiTNF vs vedolizumab-ustekinumab) after antiTNF failure, using descriptive and comparative statistics. Results: The cohort comprised 145 patients. Demographic and clinical characteristics are represented in Table 1. A total of 232 biologic therapies were indicated. Of the total cohort, 60 (41.3%), 21 (14.4%) and 6 (4.1%) used two, three and four lines, respectively. Biologics used were Infliximab (n=95), Adalimumab (n=69), Vedolizumab (n=35), Ustekinumab (n=26) and Golimumab (n=7). Therapy characteristics, clinical effectiveness, need for intensification, discontinuation, and therapy duration for each biological therapy are represented in Table 2. Global rates of clinical remission, response, non-response and loss of response to a first biologic were 21.8%, 27.5%, 21.1% and 29.6%. Female gender was the only factor associated with effectiveness to a first biologic in univariate analysis (OR 2.16, CI 1.08–4.32, p 0.027). There were no significant differences regarding efectiveness between type of pouch disorder (pouchitis vs CDP, 51.6 vs 47.6%, p 0.48) or biologic agents. Thirty-nine patients received a second biologic after prior antiTNF failure (28 a second antiTNF and 11 non-antiTNF: 6 Vedolizumab, 5 Ustekinumab). Basal characteristics in this subgroup showed no significant differences. Clinical response (21.4 vs 63.6%, p 0.02) and discontinuation therapy rates (82.2 vs 54.5 %, p 0.04) after 11 months showed a more favorable profile for non-antiTNF therapy. Conclusion: Biologics represent an effective option in the management of pouchitis and Crohn′s like disease of the pouch. Despite our small sample size, non-antiTNF therapy could be the best option after antiTNF failure. 1 Fernando Magro. J Crohns Colitis 2017; 11(6): 649–670.